2018
DOI: 10.1021/acs.jpcc.8b02697
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Charge-Transfer Dynamics in the Carotenoid–Porphyrin–C60 Molecular Triad Solvated in Explicit Tetrahydrofuran and Its Spectroscopic Signature

Abstract: We investigated the charge-transfer dynamics between distinctive excited states of a carotenoid–porphyrin–C60 molecular triad in tetrahydrofuran solvent. Our approach combines all-atom molecular dynamics simulations with an explicit solvent and electronic-state-specific force fields with a recently proposed hierarchy of approximations based on the linearized semiclassical method. The validity of the second-order cumulant approximation, which leads to a Marcus-like expression for the rate constants, was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 83 publications
3
71
1
Order By: Relevance
“…This has already been observed for Marcus theory rate constants in Ref. 44. However, the initial rate coefficient in the rigid bent triad is higher than that in the flexible bent triad, which can be traced back to structural differences in the equilibrated ground state.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This has already been observed for Marcus theory rate constants in Ref. 44. However, the initial rate coefficient in the rigid bent triad is higher than that in the flexible bent triad, which can be traced back to structural differences in the equilibrated ground state.…”
Section: Resultssupporting
confidence: 71%
“…33,43 Recently, we used the LSC E-FGR to estimate the CT rate constants between the three excited states of the carotenoid-porphyrin-C 60 (CPC 60 ) molecular triad solvated in explicit tetrahydrofuran (THF). 44 It was found that the CT rate constants are strongly dependent on the conformation of the triad, and that CT in the linear conformation is faster than in the bent conformation. 15,44 It was also found that CT is driven by the solvent DOF, rather than by the intramolecular triad DOF.…”
Section: Introductionmentioning
confidence: 99%
“…Electronically nonadiabatic dynamical processes constitute an important class of inherently quantum-mechanical chemical phenomena that range from electronic energy and charge transfer to photochemistry. [1][2][3][4][5][6][7][8][9][10][11][12] Electronically nonadiabatic dynamics also underlie the functionality of many technologically-and biologically-relevant systems ranging from photovoltaic devices [12][13][14][15] to the photosynthetic reaction center. [16][17][18] The prohibitive computational cost of quantum-mechanically exact simulations of electronically nonadiabatic dynamics in complex molecular systems [19][20][21][22] has led to the development of a wide variety of approximate approaches, 23 including the Ehrenfest method, 24 surface hopping methods, [25][26][27][28][29][30][31][32][33][34][35][36] the mixed quantum-classical Liouville method, [37][38][39][40][41][42][43]…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Like the natural process, there are many artificial systems in which the photoinduced charge transfer plays a crucial role. [8][9][10][11][12][13][14][15] Examples include PICT in dye-sensitized solar cells, [8][9][10][11][15][16][17] ultra-fast charge-transfer in organic photovoltaic systems, [12][13][14]18,[18][19][20][21][22][23][24][25] photocatalytic electron/hole transfer in "colloidal quantum dot-organic molecule complex" interfaces, [26][27][28] and photoinduced proton-coupled electron transfer. [29][30][31] Understanding the detailed charge transfer dynamics will provide valuable mechanistic insights and design principles for next-generation photocatalytic devices, and profoundly impact energy production and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach uses the fewest switches surface hopping algorithm 32,33 to capture the influence of nuclear vibrations on the electronic nonadiabatic transitions, and the single-particle timedependent Kohn-Sham (TDKS) approach 8,34,35 to describe the quantum mechanical state of the transferring electron. With this approach, we investigate the non-adiabatic PICT dynamics in phthalocyanine dimer/fullerene system 12,18,36 and Carotenoid-Porphyrin-C 60 (CPC) triad system, 13,19,22,23,[37][38][39] which are model systems for understanding the CT dynamics in organic photovoltaics. Our results are in excellent agreement with both experimental measurements and highlevel (yet expensive) theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%